2006
DOI: 10.1111/j.1365-3040.2006.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and developmental effects on the biosynthesis of UV‐B screening pigments in Scots pine (Pinus sylvestris L.) needles

Abstract: The major UV-B screening pigments of the epidermal layer of Scots pine ( Pinus sylvestris ) needles are flavonol 3-oglycosides (F3Gs) esterified with hydroxycinnamic acids at positions 3 ¢¢ and 6 ¢¢ . Acylation is the last step in biosynthesis and is catalysed by position-specific hydroxycinnamoyl transferases (3 ¢¢ and 6 ¢¢ HCT). The UV-B dependence of these enzyme activities was studied in primary needles of Scots pine seedlings grown under different UV-B conditions in environmentally controlled sun simulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…6). This trend is in agreement with results from Kaffarnik et al (2006) who showed that under field conditions, the concentration of soluble DCA increased sharply during early needle development and continuously decreased until the end of the second growing season, likely due to its progressive translocation to the cell wall. Diacylated flavonol glycosides, and particularly DCA, are efficient UV-screening pigments.…”
Section: Uv-induced Modulation Of the Soluble Phenolic Compositionsupporting
confidence: 92%
“…6). This trend is in agreement with results from Kaffarnik et al (2006) who showed that under field conditions, the concentration of soluble DCA increased sharply during early needle development and continuously decreased until the end of the second growing season, likely due to its progressive translocation to the cell wall. Diacylated flavonol glycosides, and particularly DCA, are efficient UV-screening pigments.…”
Section: Uv-induced Modulation Of the Soluble Phenolic Compositionsupporting
confidence: 92%
“…1 and 3). Other authors also report that both UV and high PAR can induce flavonoid accumulation (G€ otz et al, 2010;Kaffarnik et al, 2006). Thus, our results reinforce the importance of taking both PAR and UV acclimation into consideration when considering plant responses to UV-B radiation (Krizek, 2004;G€ otz et al, 2010).…”
Section: Light Induced Accumulation Of Flavonoidssupporting
confidence: 91%
“…8). A similar behavior has been described in 60-year-old European beech in a free-air chronic ozone field study (Bahnweg et al 2005), as well as in mature Scots pine and Norway spruce trees, where a deposition of the soluble fraction into cell walls during leaf ontogeny has been suggested (Heilemann and Strack 1990; Kaffarnik et al 2006). In the present study, we observed the appearance of 3,3 0 ,4,4 0 -tetramethoxybiphenyl in response to ozone exposure.…”
Section: Discussionsupporting
confidence: 71%